Quantifying Pollutants from Household Wastewater in Kuching, Malaysia - Ling, Teck Yee; Siew, Tuck-Fatt; L., Nyanti (IDOSI Publication, 2010)
In Malaysia, septic tank effluents were discharged into rivers. However, knowledge on quantity of household wastewater pollutants was incomplete. Therefore, water constmlption, wastewater flow and pollutants concentrations and loadings were investigated The residential areas studied were the high income area of De Summit Condominium (DS), medium income areas of Tabuan-Jaya (IJ) and Taman Satria-Jaya (TSJ) and low income areas of RPR Batu-Kawa (RPR) and Taman Malihah (TM). Results indicated that wastewater flows ranged from 95-122 L/c/d which were 33-67% of the water consumption rates. DO and BOD ranged from 0.7-4.4 mgtl and 67-135 mg/L respectively. Nitrate-nitrogen was the highest at DS (0.19 mg/L). Reactive phosphorus ranged from 4.4-12.7 mg/L. In all areas, E. coli ranged from 10-10 cfu/100mL. Mean loadings of BODs, reactive-phosphorus, nitrate-nitrogen and E. coli were found to be 8-14 glc/d, 0.6-1.0 g/c/d, 4.3-9.6 mg/cld and 3.3-7.2x109 CFU/c/d respectively. Reactive phosphorus loading was 1.6 times higher in the low income areas (RPR and TM) when compared to the other areas. With the area population of 44,515, 10x10 L/d of water was consumed, 5x10 L/d of wastewater produced contributing to 511 kg/d of BOD, 31 kg/d of reactive phosphorus, 1.8x10 E. coli/d to surface water around Kuching.